Análise da produtividade de insumos modernos na produção de cacau - de Souza Menezes, José Alexandre; Paniago, Euter; Pereira Ladeira, Hércio; Lima Bandeira, Antônio (Revista Ceres, 2025)
The present study considers the utilization of the modern inputs recommended by CEPLAC in cocoa production, at the farm level in southern Bahia during the agricultural year 1971/72.